Impact of Using the INTUSTEL Model in Creative Thinking and the Acquisition of Performing Some of the Football Skills by Students - Soran, Entethar Faroq Allyas; Garash, Stefan Jajo Marzena (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. To investigate the impact of applying the traditional lesson on creative thinking and acquisition of performing some of the football skills among the control group students. To explore the effect of applying the INTUSTEL model on creative thinking and acquisition of performing some of the football skills among the experimental group students. The experimental method was adopted to meet the research requirements. Materials and methods. The research population consisted of intermediate-stage Mariam Al-Adhraa Secondary School for the academic year (2023-2024) in the district of Al-Hamdaniya. As for the sample, it was limited to students selected randomly through a lottery, totalling (48) female students. A number of sample members were excluded due to their lack of homogeneity. Thus, the research sample became (40) female students for each of the selected divisions. They were randomly distributed into two groups, each group having (20) female students. The experimental group used the INTUSTEL method, and the control group used the traditional method. Results. The results of the arithmetic average for the experimental sample before and after applying the (INTUSTEL) model in four variables (creative thinking (56.100, 68.500), dribbling (24.262, 19.762), passing (0.050, 16.250), and scoring (6.600, 8.750)) show a significant difference in favouring to the experimental group after applying the INTUSTEL model. That indicated the effectiveness of the INTUSTEL model in physical education, and improvements in the performance levels of the selected skills were observed when applied by the students. Conclusions. The experimental group that used the INTUSTEL method outperformed the control group that used the traditional method in creative thinking and acquisition of a number of football skills for female students. This improvement results from the student’s participation in the educational unit, where they chose the exercises designated by the teacher to develop the selected skills based on their abilities.